2020
DOI: 10.1016/j.pdpdt.2020.101995
|View full text |Cite
|
Sign up to set email alerts
|

UV-C (254 nm) lethal doses for SARS-CoV-2

Abstract: Highlights We developed a controlled assay to investigate the UV-C inactivation kinetics for SARS-CoV-2. We established the UV-C lethal doses for the virus in vitro . LD 90 for SARS-CoV-2 was reached at 0.016 mJ/cm 2 . LD 99.999 was achieved at 108.714 mJ/cm 2 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 6 publications
6
70
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first paper on SARS-CoV-2 describing the effect of UV-C on different infected materials together with the physiological viral infectivity decay as well. As for virus survival tests, other studies previously evaluated the effect of UV-C light on SARS-CoV-2 inactivation by using different experimental conditions often consisting in higher virus inoculums (50 to 600 µL) [16][17][18]42,43] in respect to our approach that should be closer to possible scenarios of surfaces contamination. Indeed, the UV-C doses found to reduce the viral titer of about 3 logs (99.9% reduction) were much higher than ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first paper on SARS-CoV-2 describing the effect of UV-C on different infected materials together with the physiological viral infectivity decay as well. As for virus survival tests, other studies previously evaluated the effect of UV-C light on SARS-CoV-2 inactivation by using different experimental conditions often consisting in higher virus inoculums (50 to 600 µL) [16][17][18]42,43] in respect to our approach that should be closer to possible scenarios of surfaces contamination. Indeed, the UV-C doses found to reduce the viral titer of about 3 logs (99.9% reduction) were much higher than ours.…”
Section: Discussionmentioning
confidence: 99%
“…UV-C light induces chemical modifications of nucleic acids, leading to the blocking of replication mechanisms [ 15 ]. SARS-CoV-2 is highly susceptible to UV-C irradiation, and different studies demonstrated the rapid inactivation of the virus on surfaces and supplies [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of the included studies are reported in Table I. Most of the studies (n = 8) were conducted in the United States [33][34][35][36][37][38][39][40], one of which also in Korea [40], four in Japan [41][42][43][44], two in Italy [45,46], and one each in China [47], Israel [48], Germany [49], and Brazil [50].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…They were published between 1972 and 2020, with three published before 2000 [34,37,44] and J o u r n a l P r e -p r o o f eight published in 2020 [35,38,39,41,43,[48][49][50]. All were experimental studies, conducted in laboratory settings: four focused on SARS-CoV-1 [36,42,45,47], one study on MERS-CoV [33], three on seasonal human coronaviruses [34,35,48] and six on SARS-CoV-2 [38,39,41,43,49,50].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Mitigating transmission of SARS-CoV-2 in water is thus critical in both developed or developing countries. Current chemical and germicidal ultraviolet light (i.e., UV 254 ) disinfection strategies can be well managed in centralized water and wastewater treatment plants to inactivate SARS-CoV-2 (3, 5). These strategies are almost impossible to be implemented at the household or community levels, where raw sewage, unsealed sewer vent pipes, leaking septic systems, medical biological wastes, etc.…”
Section: Introductionmentioning
confidence: 99%